Mapeando redes, diversificando olhares: construções e perspectivas sobre a rede de enfrentamento a violência contra a mulher em Santa Maria - Flores, Letícia Bortolotto (2019)
Violence against women is multidimensional and multidetermined, so attention to women in situations of violence must account for this complexity through an articulated network that represents women's needs. Although the documents that support networking are structured from the guidelines of transversality and intersectoriality, the attention given to women does not seem to occur as planned. In this sense, the purpose of this research was to analyze which are and how are the strategies linked to the Combat Network of Violence Against Women in the city of Santa Maria/RS mapping the strategies and understanding the conditioning factors for the development of actions. Data collection was developed through Snow Ball sampling method, allowing the participants to make indications from their closest contacts to continue the collection. In addition, notes were used in Field Diary. The seed choice of the study was the Specialized Police for Assistance to Women (DEAM) of Santa Maria. Eleven semi- structured interviews were completed, with participants from specialized and non-specialized services that make up the Combat and Assistance Network for Violence against Women, as well as actors involved with other coping strategies. The analysis of content listed categories a priori, based on documents and booklets related to the combat policies of violence against women in the Public Prosecutor's Office, and a posteriori with constructed from the examination of the contents of the interviews. The presentation of the results and discussion about the data was constituted in two articles. The main results converged to the lack of financing and the not structuring of the network. In practice, the perspective of working in networks is being built informally from contacts between several actors that make up the fronts of Attendance and Confrontation of politics. The reduction of investment and the nonexistence of services that have an important role of articulation, such as a Women's Reference Center, directs the State's low engagement with coping strategies, resulting in isolated and fragmented attention, according to the dominant political culture. In this way, the conclusions demonstrate the alarming process of depoliticization of gender policies, which remove the State's responsibility towards the social question and generate a distancing from the ideals of consolidation of democracy and legitimation of the State.